An Empirical overview of Microenterprises and Microfinance Development in Nepal - Sharma, Puspa Raj (Journal of Nepalese Business Studies, 2016)
This paper aims an overview of microfinance and microenterprises development and analyze the related various dimensions of the micro-enterprises. It focuses on registration status, causes of registration and non-registration, employment status and participation of women in the microenterprises, problems related to microenterprises, training need assessment and their effectiveness, microinsurance and their status. Journal of Nepalese Business Studies Vol. 9, No. 1, 2015 pp.3-12